O cuidado à criança em idade escolar: percepções de equipes da Estratégia Saúde da Família - Villardi, Marina Lemos [UNESP]; Cyrino, Eliana Goldfarb [UNESP] (Sociedade Brasileira de Medicina de Familia e Comunidade (SBMFC), 2012)
Objective: The purpose of this study was to understand how Family Health Strategy teams perceive child care at school age. Methods: This is an exploratory study with a qualitative approach. Data collection involved semi-structured interviews with 21 professionals from the Family Health Units in Botucatu, State of São Paulo, Brazil, who were asked about the health needs of children at school age and the actions taken to fulfill them. Content analysis was chosen to organize the data generated in the interviews. Results and discussion: Two categories resulted from the interviews were identified: 1) The care for children at school age, and 2) Multi-professional and inter-sectorial practices: gaps in health practices. Health professionals recognized the shortage of health interventions for children at school age and clearly expressed how they must be cared for, as opposed to how, in practice, these actions were limited and disarticulated. Multi-professional and inter-sectorial practices were considered essential in the care for children at school age; however, they were described as fragmented. Final consideration: It was possible to identify that the perceptions of what is needed for children at school age are insufficient for Family Health Strategy teams to mobilize themselves or incorporate health care practices to those children.

Objetivo: Comprender las percepciones de los profesionales de los equipos de salud de la Estrategia de Salud de la Familia sobre el cuidado de los niños en edad escolar. Métodos: Se trata de un estudio exploratorio con enfoque cualitativo. Se entrevistaron 21 profesionales de las Unidades de Salud Familiar del municipio de Botucatu usando entrevistas semi-estructuradas acerca de las necesidades de salud de los niños en edad escolar y de las acciones realizadas frente a tales necesidades. Para organizar los datos generados en las entrevistas, se eligió el análisis de contenido. Resultados y discusión: Se identificaron dos categorías de análisis que surgieron de las declaraciones de los entrevistados: El cuidado de los niños en edad escolar, Multiprofesionalismo e intersectorialidad: deficiencias en las prácticas en salud. Los profesionales de la salud reconocen la falta de acciones en salud para niños en edad escolar y explicitan cómo debe ser ese cuidado, pero la práctica se revela limitada y desarticulada. Las actividades multiprofesionales e intersectoriales son destacadas como fundamentales para el cuidado de los niños en edad escolar, sin embargo, se presentan como fragmentadas. Consideraciones finales: Fue posible identificar que percibir las demandas de los niños en edad escolar no es suficientes para que los Equipos de Salud de la Familia se movilicen o incorporen prácticas de cuidado de la salud de los niños.

Objetivo: Compreender as percepções dos profissionais das equipes de saúde da Estratégia Saúde da Família sobre o cuidado à criança em idade escolar. Métodos: Trata-se de estudo exploratório com abordagem qualitativa. Para coleta de dados, utilizou-se entrevista semiestruturada com 21 profissionais de Unidades de Saúde da Família do município de Botucatu sobre as necessidades de saúde da criança em idade escolar e ações realizadas para elas. Para a organização dos dados gerados nas entrevistas, elegeu-se a análise de conteúdo. Resultados e discussão: Foram identificadas duas categorias de análise que emergiram das falas dos entrevistados: O cuidado à criança em idade escolar; Multiprofissionalidade e intersetorialidade: lacunas nas práticas em saúde. Os profissionais de saúde reconhecem a carência de ações em saúde para a criança em idade escolar e explicitam como deve ser esse cuidado, porém a prática revela-se limitada e desarticulada. As atividades multiprofissionais e intersetoriais são destacadas como fundamentais para o cuidado à criança em idade escolar, no entanto, são apresentadas como fragmentadas. Considerações Finais: Foi possível identificar que as percepções das demandas da criança em idade escolar não são suficientes para que Equipes de Saúde da Família se mobilizem ou incorporem práticas de cuidado à saúde para elas.
The care for school-aged children: perceptions of Family Health Strategy Care teams
El cuidado de los niños en edad escolar: percepciones de los equipos equipos de la Estrategia de Salud de la Familia
Keywords: School health; Family health strategy; Child care; Child health services; Child; Saúde escolar; Estratégia saúde da família; Cuidado da criança; Serviços de saúde da criança; Criança